Food aid distribution in Bangladesh: leakage and operational performance - Ahmed, Akhter; Rashid, Shahidur; Sharma, Manohar; Zohir, Sajjad (International Food Policy Research Institute, 2004)
The International Food Policy Research Institute (IFPRI) conducted a comprehensive study of the efficiency of food distribution in food aid-supported programs in Bangladesh. The capacity and efficiency of the food distribution system was assessed from entry ports to targeted beneficiaries. The study identified problems in the whole food distribution system, determined the level of losses, leakages, and other lapses at various stages, and recommended solutions. The study has three components: (1) food discharge at harbors, (2) the public food distribution system, and (3) food distribution to program beneficiaries. This brief summarizes the main findings and a few of the many key recommendations of the third component of the study.